Social Smoking: Implications for Public Health, Clinical Practice, and Intervention Research - Schane, Rebecca E. (2009)
BACKGROUND: Social smoking is increasingly prevalent and poses a challenge to traditional cessation practices. Tobacco companies conducted extensive research on social smokers long before health authorities did and marketed products to promote this smoking behavior. PURPOSE: Research is described and mechanisms identified that are used to promote social smoking to help improve cessation strategies in this growing group. EVIDENCE ACQUISITION: Searches from 2006 to 2008 of previously secret tobacco industry documents using keywords social smoker, light smoker, casual smoker, youth smoker, and occasional smoker, followed by snowball searching. Data analysis was conducted in 2008. EVIDENCE SYNTHESIS: Tobacco industry research identified characteristics of social smokers that include: (1) denial of personal nicotine addiction; (2) self-categorization as a nonsmoker; (3) propensity for decreased tobacco use in response to smoke-free laws; (4) variations in age, education, ethnicity, and socioeconomic backgrounds; and (5) a perceived immunity to personal health effects of tobacco but fear of consequences to others. Tobacco companies developed marketing strategies aimed at social smokers, including “non–habit forming” cigarettes. CONCLUSIONS: Previously considered a transient behavior, social smoking is also a stable consumption pattern. Focused clinical questions to detect social smoking are needed and may include, “Have you smoked any cigarettes or used any tobacco products in the past month?” as opposed to “Are you a smoker?” Clinicians should recognize that social smokers might be motivated to quit after education on the dangers of secondhand smoke rather than on personal health risks or with pharmacotherapy.